An umbrella review and meta-analysis of the use of renin-angiotensin system drugs and COVID-19 outcomes: what do we know so far?. (1st April 2022) - Mueller, T; Weir, N M; Kurdi, A
Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is caused by the "severe acute respiratory syndrome coronavirus 2" (SARS-CoV-2), and commonly presents with fever, loss of smell/taste, and a persistent cough; in severe cases, patients require hospitalisation and external ventilation. Advanced age and pre-existing conditions such as cardiovascular diseases and diabetes have been associated with an increased risk of COVID-19 related mortality. Based on their mechanisms of action and widespread use among patients at high risk of poor disease outcomes, the impact of renin-angiotensin-aldosterone system (RAAS) inhibitors – including angiotensin converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) – on COVID-19 related outcomes has become a topic of interest, resulting in rapid dissemination of a large number of predominantly retrospective, observational studies since early 2020. Since many of these studies were limited in scope and results were inconclusive, systematic reviews and meta-analyses of published and unpublished findings swiftly followed. Aim: To assess the effect of ACEIs and ARBs on COVID-19 related outcomes by summarising the currently available evidence. Methods: Umbrella review of systematic reviews and subsequent meta-analysis. Eligible for inclusion were systematic reviews with meta-analysis focusing on patients with or without COVID-19 exposed to ACEIs and/or ARBs compared to patients not exposed to the medication. Outcomes of interest included risk of infection; hospitalisation; severity; and death. Reviews were identified through a literature search in Medline, EMBASE, Scopus, the Cochrane database of systematic reviews, and medRxiv, from 2019 until 1st of February 2021. Data was extracted using a standardised extraction sheet; the AMSTAR 2 Critical Appraisal Tool for systematic reviews was used for quality assessment. Heterogeneity between studies was evaluated using I 2 statistics, and findings of included meta-analyses were summarised using random-effects models. The protocol was registered with PROSPERO (CRD42021233398). Results: Out of an initial 157 publications, 66 systematic reviews underwent full text screening; after further exclusions based on pre-specified criteria, 47 studies were identified to be relevant. The number of included studies as well as the outcomes of interest varied widely between reviews, with death being the most common. Odds ratio for risk of COVID-19 infection among patients treated with ACEIs/ARBs versus patients not on treatment was 0.99 (95% Confidence Interval (CI) 0.97 – 1.02; 19 studies, I 2 = 24.7%); and for hospitalisation among COVID-19 patients treated with ACEIs/ARBs versus not on treatment, 1.23 (95% CI 1.04 – 1.46; 11 studies, I 2 = 76.4%); severe disease 0.86 (95% CI 0.78 – 0.95; 28 studies, I 2 = 68%); and death, 0.80 (95% CI 0.75 – 0.86; 47 studies, I 2 = 51.9%). Conclusion: While treatment with ACEIs or ARBs does not appear to impact the risk of COVID-19 infection, it appears that patients on treatment have lower risks of severe disease and mortality compared to patients not on ACEIs/ARBS treatment. Findings should be interpreted cautiously as the systematic reviews/meta-analyses included in this study were of variable quality, and there was high heterogeneity among studies for most outcomes. Findings will inform evidenced-based guidelines on the appropriate measures for patients at risk of COVID-19 infection and prescribed RAAS inhibitors.